Development of Diagnostic Assessment of Critical Thinking Skills in Four-Level Format on Kinematics Material - Setiawan, Doni (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The aim of this research is to develop a four-level critical thinking skills assessment that is valid and reliable. The assessment was developed based on four factors of critical thinking skills, namely explanation, analysis, conclusion and evaluation. This research is classified as development research (R&D). The research sample was 52 students in class XI of Nahdlatul Ulama High School, Tegal City. Data analysis methods include: expert validation, construct validity, and assessment reliability. Expert validation by two lecturers and two physics teachers, construct validity test with factor analysis consisting of: One-Sample K-S Test, KMO MSA test, correlation between variables (Anti-Image Correlation), communality, and Total Variance Explained. The results of the expert test analysis obtained an average questionnaire score of 78.8% with high validity criteria. The results of the One-Sample K-S Test for critical thinking skills assessment were 0.261, so it was concluded that the data was normally distributed. The results of the adequacy test via the KMO MSA value are 0.000, so factor analysis can be carried out. The results of the Total Variance Explained analysis in the scree plot diagram obtained 4 points where the eigenvalue was greater than 1.00, so that 4 factors were obtained which proved that the assessment had 4 component aspects of critical thinking skills as assessment factors. The reliability test of the assessment obtained a Cronbach's alpha coefficient value of 0.693, so it was found that the diagnostic assessment of critical thinking skills developed was reliable. The assessment developed is not only able to describe students' critical thinking skills, but is also able to provide an overview of how each aspect of critical thinking skills supports each other. The assessment developed is suitable for use as an instrument to measure critical thinking skills and the relationship of each aspect of students' critical thinking skills to kinematics material.